Pengembangan Modul Matematika Berbasis Contextual Teaching Learning pada Siswa Kelas IV 48 Lubuklinggau - Endang Fitri Utami; Elya Rosalina; Aren Frima (Indra institute Research & Publication, 2022)
This study aims to develop a product in the form of a mathematics module based on Contextual Teaching Learning for fourth grade elementary school students in accordance with the 2013 curriculum and produce valid, practical and effective modules for use in learning.This research is a development research with a four-D development model. Based on the results of the analysis of assessments by the three experts, namely: 80 linguists, 90 media experts, 95 material experts, it shows that the contextual teaching learning- based mathematics module on statistical material meets the very valid criteteria.While the results of the research on teacher practicality sheets obtained an average of 87,5% and students consisting of 6 people obtained an average of 93,3% that the Contextual Teaching Learning-based Mathematics Module met the very practical criteria. And the results of the research on the effectiveness of all fourth grade students showed that the Mathematics Module based on Contextual Teaching Learning met the criteria for being quite effective with a final score of 75, so it can be concluded that the Mathematics Module based on Contextual Teaching Learning statistical material met the criteria of being valid, practical and effective and could be used in learning.